Analisis Kemiskinan Petani Padi di Desa Bumiharjo Kecamatan Batanghari Kabupaten Lampung Timur Tahun 2017 - Umi Latifah; Buchori Asyik; Edy Haryono (JPG (Jurnal Penelitian Geografi), 2017)
This studied to examine about: The status of land ownership of rice farmers, the average land area of rice farmers, the average income of paddy farmers, the average number of dependents of paddy farmers. This research used descriptive method, population amounted to 249 rice farmers, samples taken by 25 percent that is 62 rice farmers selected used simple random sampling technique. Methods of data collection used observation techniques, structured interview techniques and documentation techniques. The data analysis technique used is the percentage table. The results of this studied indicate that (1) as many as 83,87% of rice farmers worked on their own land and 16,13% of rice farmers worked on land not own. (2) The average land area employed by rice farmers is 0,26 ha. (3) The average income of paddy farmers is Rp 635.269 per moon. (4) The average number of dependents of rice farmers is 5 people.Penelitian ini bertujuan untuk mengkaji tentang: Status kepemilikan lahan garapan petani padi, rata-rata luas lahan garapan petani padi, rata-rata pendapatan petani padi, rata-rata jumlah tanggungan petani padi. Penelitian ini menggunakan metode deskriptif, populasi berjumlah 249 petani padi, sampel yang diambil sebesar 25% yaitu 62 petani padi dipilih menggunakan teknik simple random sampling. Teknik pengumpulan data menggunakan teknik observasi, wawancara terstruktur dan dokumentasi. Teknik analisis data menggunakan tabel persentase. Hasil penelitian ini menunjukkan bahwa (1) sebanyak 83,87% petani padi menggarap lahan milik sendiri dan 16,13% petani padi menggarap lahan bukan milik sendiri (sakap). (2) Rata-rata luas lahan yang digarap petani padi 0,26 ha. (3) Pendapatan rata-rata petani padi sebesar Rp 635.269 perbulan. (4) Rata-rata jumlah tanggungan petani padi sebanyak 5 orang.Kata kunci: kepemilikan lahan, luas lahan, pendapatan